Corrosão e tribocorrosão de novas ligas Ti35Nb5Zr e Ti35Nb10Zr em saliva artificial - Ribeiro, Ana Lúcia Roselino [UNESP] (2012)
The long-life success of dental implants relies on the interaction between the biomaterial and oral environment, always involving electrochemical reactions, mechanical stresses and mechanical wear. In order to improve the mechanical strength and corrosion resistance of titanium (Ti), alloying elements are added to it, the most common alloy being Ti6Al4V. However, vanadium and aluminum are known to be toxic. Therefore, in last years, efforts are being made towards the development of new high resistant and biocompatible titanium alloys, namely from the TiNbZr system. Therefore, the aim of this work was to assess the corrosion and tribocorrosion behavior of new Ti35Nb5Zr and Ti35Nb10Zr in artificial saliva at 37°C, in comparison with the commercial Ti6Al4V alloy. Open circuit potential (Ecorr) and electrochemical impedance spectroscopy (EIS) experiments were carried in function of time (0-216h). Tribocorrosion tests were performed at different applied loads (50mN to 1N) both at Ecorr and anodic applied potential. In general, all alloys exhibited an increase of Ecorr with the immersion time, indicating the growth and stabilization of the passive film. The EIS results indicated that Ti35Nb10Zr alloy exhibited slightly better corrosion resistance than Ti6Al4V. Just as better tribocorrosion behavior at low applied loads. Therefore, the passive film formed on Ti35Nb10Zr alloy had better mechanical strength and corrosion resistance due to Nb2O5 e ZrO2. However, the bulk metal of Ti6Al4V suffered less mechanical wear. Concluding, Ti35Nb10Zr alloy appear as promising candidate for dental implant-abutment sets manufacturing.